A STUDY OF SERVICE QUALITY AND TRANSPORTATION EFFICIENCY AFFECING DECTING DECISION TO USE REPEAT SERVICES OF THAI POST SERVICE UESRS, NAKHON SAWAN PROVINCE - Pharitpongsakorn, Kanha (Journal of MCU Nakhondhat, 2021)
The objectives of this research were to 1) To know the personal information of users of Thailand Post Service in Nakhon Sawan Province 2) To know the relationship between service quality of Thai Post Office in Nakhon Sawan Province and the decision to use repeat services of thai post service users. 3) To know the relationship between the transportation efficiency of the Thai Post Office, Nakhon Sawan Province and the decision to use repeat services of thai post service users. This is a Quantitative Research (survey research). The research samples were 400 consumer of Thai Post Office service in Nakhon Sawan Province. The data were collected from September to October 2020 by Questionnaires. The research instrument was a questionnaire from which the collected data were analyzed using Frequency, Percentage, Mean, Standard Deviation and Multiple Linear Regression Analysis (Enter method) with the statistical significance level at 0.05. The results showed that 1) The sample mostly were females, those aged from 20 - 35 years. Most of them graduated with bachelor's degree level. Most of the users are company employee and students. They received monthly income of lower 15,000 baht, the most popular postal services that they are often use are express delivery. They are delivery parcel by Thai Post Office in Nakhon Sawan Province once a month. 2) Quality of Service of Thai Post Office in Nakhon Sawan Province in terms of Equitable Service, Continuous Service, and Progressive Service was a relationship and a positive impact on the decision to use repeat services of thai post service users at the significant level of 0.05. 3) Transportation efficiency of Thailand Post, Nakhon Sawan Province in terms of Economy, Safety, Convenient, and Certainty & Punctuality was a relationship and a positive impact on the decision to use repeat services of thai post service users at the significant level of 0.05.